REKOMENDASI STRATEGI PENGEMBANGAN BISNIS “RUMAH LULUR SALON WANITA” - Mulya Fuji Astuti; Didip Diandra (Jurnal Manajemen dan Bisnis, 2021)
The shopping pattern may change selectivity based on the differences in customers view toward a product or service offered. In order to grow, the company must be able to create a competitive advantage in the form of good quality service to the consumers.This reseach use to analyze the development of the business of Rumah Lulur  Salon Wanita, the first ever SPA for women available in the City of Ternate. The purpose of this reseach is to reveal the obstacles and challenges faced and how to overcome them with suitable business strategies. This research used a qualitative study analysis with an explotarative method by interview the owner observes the location. The result of analysis shows that some key factors that can be applied in the future for the development of Rumah Lulur Salon Wanita are: First, design business strategy through 7P’s Marketing Mix (Service, Physical Evidence, Promotion, and People). Second, develop the business model canvas through the value proposition and key partners.